Comparison of bone health status, muscular performance and anaerobic capacity between physically active hikers and sedentary individuals - Zarian, Nur Syara Afiqa (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
This study was carried out to determine the differences in bone health status, muscular performance, and anaerobic capacity among physically active hikers and sedentary individuals. A total of 32 participants (N=32) consists of 16 physically active hikers (hikers group, n=16) and 16 sedentary individuals (sedentary group, n=16) with ages between 20-25 years old with normal BMI values (18-24.9 kg/m2) were recruited in this study. All participants were required to perform the following physical assessments: anthropometric and body composition was measured by stadiometer scale and body composition analyzer, anaerobic capacities were measured by Cycle ergometer, isokinetic muscle strength and power were measured using BIODEX dynamometer with 3 different angular velocities of movement, i.e. 600.s-1, 1800.s-1 and 3000.s-1 on both dominant and non-dominant arm and leg. Handgrip strength was measured via a Hand dynamometer. Moreover, a bone sonometer was used to measure the bone speed of sound (SOS) which can reflect the bone mineral density of radius and tibia bone. The result showed that there were statistically significantly greater values (p<0.05) of isokinetic knee flexion peak torque per body weight (PT/BW) at 3000.s-1 angular velocity, shoulder extension peak torque (PT) at 3000.s-1 angular velocity, shoulder flexion PT/BW at 3000. s-1 angular velocity and shoulder flexion PT at 1800.s-1 angular velocity in the hiker group than the sedentary group. However, statistically,significant differences were not observed in other parameters between the hiker group and sedentary group. From the results, it can be concluded that involvement in hiking can improve muscular strength compared to a sedentary lifestyle and implying the benefits of hiking at the recreational stage compared to a sedentary lifestyle.